Thailand’s Minimum Wage Increase of 2013: Impacts on Foreign Direct Investment - Fuangfoo, Aikaparb Michael (International Journal of Economics and Financial Issues, 2018)
This analysis investigates possible foreign direct investment (FDI) impacts and initial shock due to Thailand’s 39.5 percent minimum wage increase in 2013. Determining FDI factors and influences after the nationwide policy was implemented is important because wages are a vital component of foreign investment. Thailand holds a certain competitive advantage due to relatively low wages compared to certain countries, which could have an impact on FDI. FDI can be gauged as a measurement for the presence of multinational corporations (MNCs) and may be interpreted as a level of influence in the country; Thailand’s economy and long-term growth relies heavily on FDI which could foster increases in technology transfers, infrastructure, and quality of living. Keywords: Foreign Direct Investment, Minimum Wage, Multinational Corporations, Technology Transfers, Protectionism, Trans-Pacific Partnership JEL Classifications: E22, E24, F14, F16, F21, F23, P45